Our Body Our Health (Jirkeena, Caafimaadkeena): Somali Women’s Narratives on Sexual Health - Connor, Jennifer Jo; Abdi, Cawo; Chen, Muzi; Salad, Munira; Pergament, Shannon; Afey, Foos; Hussein, Intisar; Robinson, Beatrice “Bean” E. (The Journal of sex research, 2025)
Women across the globe have been subject to female genital cutting (FGC), with the highest rates in Somalia. FGC can result in sexual concerns, especially sexual pain and lower pleasure. Due to ongoing civil war and climate disasters, there is a large number of Somali immigrants and refugees living in countries where healthcare providers may be unfamiliar with the impact of FGC. In this qualitative study, sixty Somali women between the ages 20 and 45 and living in the U.S. shared their perspectives on how FGC has affected their sexual lives, including how they have coped with any complications attributed to FGC. Participants were recruited through convenience sampling and interviewed by a bilingual community researcher in either Somali or English. Data were analyzed through a participatory analysis process by academic and community researchers. Themes included sexual desire, arousal, and pleasure; sexual satisfaction; sexual pain at first intercourse; coping with sexual pain at first intercourse; long-term sexual pain, coping with long-term sexual pain. Results are discussed with a focus on agency of the participants, role of partners, and implications for healthcare professionals.